Hexavalent-Chromium-Induced Oxidative Stress and the Protective Role of Antioxidants against Cellular Toxicity - Veer Singh; Nidhi Singh; Manisha Verma; Rashmi Kamal; Ritesh Tiwari; Mahesh Sanjay Chivate; Sachchida Nand Rai; Ashish Kumar; Anupama Singh; Mohan P. Singh; Emanuel Vamanu; Vishal Mishra (MDPI AG, 2022)
Hexavalent chromium is a highly soluble environmental contaminant. It is a widespread anthropogenic chromium species that is 100 times more toxic than trivalent chromium. Leather, chrome plating, coal mining and paint industries are the major sources of hexavalent chromium in water. Hexavalent chromium is widely recognised as a carcinogen and mutagen in humans and other animals. It is also responsible for multiorgan damage, such as kidney damage, liver failure, heart failure, skin disease and lung dysfunction. The fate of the toxicity of hexavalent chromium depends on its oxidation state. The reduction of Cr (VI) to Cr (III) is responsible for the generation of reactive oxygen species (ROS) and chromium intermediate species, such as Cr (V) and Cr (IV). Reactive oxygen species (ROS) are responsible for oxidative tissue damage and the disruption of cell organelles, such as mitochondria, DNA, RNA and protein molecules. Cr (VI)-induced oxidative stress can be neutralised by the antioxidant system in human and animal cells. In this review, the authors summarise the Cr (VI) source, toxicity and antioxidant defence mechanism against Cr (VI)-induced reactive oxygen species (ROS).